(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Type 1 diabetes mellitus (T1DM) is a complex disease that is caused by a combination of genetic and environmental factors. One of environmental factor that has been linked to T1DM is Parvovirus B19 (B19V), a virus that can infect erythroid progenitor cell. Studies have assumed that people with T1DM are more likely to have been infected with B19V, which suggest that B19V may play a role in the development of T1DM. Objective: To detect B19V IgG in patients with T1DM. Methods: A total of 50 children with newly diagnosed T1DM and 50 non-diabetic children were recruited as controls. B19V was detected using enzyme linked immunosorbent assay (ELISA) technique. Results: B19V infections had been detected in T1DM patients and control group with exposure rate 6% and 10% respectively. However, results were statistically not-significant. Conclusion: Current study concluded that B19V infection might not be considered as a risk factor for T1DM. Keywords: Parvovirus B19, T1DM, ELISA Citation: Khudair EA, Al-Shuwaikh AM, Abdoun DS. Detection of Human Parvovirus B19 IgG in a group of Iraqi children with newly onset type 1 diabetes mellitus. Iraqi JMS. 2024; 22(2): 212-216. doi: 10.22578/IJMS.22.2.4